Studies on the potential of biological control of the anthracnose fungi Colletotrichum in Malaysian fruits. - S. Kanapathipillai, Vijaya (1990)
Anthracnose or Gloeosporium fruit rot is one of the most severe diseases in the fruit production. The causal fungus, Colletotricum species attacks fruits, flowers, stems and leaves of crops such as Avocado, Mango, beans, banana, papaya and Guava. In the pursuit of extending the shelf life of Malaysian fruits for export purposes, biological control was tried using three species of Trichoderma. In vitro studies in the laboratory show that the antagonistic species has potential as biocontrol agents as they reduce radial growth of cultures, spore germination of 6 species of Colletotricum. These fungi alfo reduced disease symptoms of anthracnose in infected banana fruits. Antagonistic action between the fungal hyphae are also observed by the use of light microscopy.